GAMBARAN PEMILIHAN POSISI PERSALINAN KALA DUA DI BPM NY. AIDA HASNANI NUHU, Amd. Keb DAWAR BLANDONG MOJOKERTO - Prasastia LD, Catur; Ahyu S, Nanda (JURNAL KEPERAWATAN SEHAT, 2015)
The selection of the labor position is used for labor pain relief during labor and can also speed up the process labor. This study was conducted from 01 May-30 July 2014. This research was descriptive sampling technique and it used purposive sampling a population of 30 respondents and a sample of 30 respondents. Data collection instruments used in the enclosed questionnaire if through a process of editing, coding, scoring, tabulating. The results of this study got as many as 18 respondents chose a half sitting position. Most of the respondents choosed the half-sitting position because they felt comfortable during childbirth. A total of 7 respondents choosed a tilted position. Respondents who are choosed it in childbirth because respondents felt loading time noticeably faster, relieve pain in the back experienced during the delivery process. A total of 2 respondents choosed crawl position. Small Part respondents chose all fours due to encouragement from family. A total of 2 resdponden also chose a sitting position. Small Part of the respondents chose the sitting position because it pushed greater strength, but sometimes this position also created a feeling of stiffness in the back because of fatigue during the childbirth. A total of 1 respondent choosed the squat position. Fewer respondents choosed the squat position with reasons suggested by health professionals dengaan certain conditions. The position of the most widely is the half-sitting position, so health workers can suggest a half-sitting position feels most comfortable position when doing labor.Keywords: election positions, labor, second stage